DETERMINATION OF APPROPRIATE PLANTING TIME OF CABBAGE VARIETIES AND HYBRIDS IN LOW SALINITY SOIL AND CLIMATE CONDITIONS OF KARAKALPAKSTAN - Alisher Juraboyevich Shokirov; Mirzagul Sersenbayevna Jadigerova (European Science Publishing, 2024)
In 2022-2023, in the weakly saline soil-climate conditions of Karakalpakstan, early-early Navruz variety of white cabbage, Magnus F 1 hybrid and mid-early Tashkentskaya 10 variety, Fresco F 1 hybrids (20.03; 30.03; 10.04; 20.04; 30.04.) planted in terms of the influence on the growth, development and productivity of plants was studied. The yield of Ertapishar Navruz variety is 4.8-15.0% higher in the variant planted on April 10 (56.2 ha/t) compared to all variants, in Magnus F 1 hybrid in the variant planted on March 30 (57.5 ha/t) all was 11.2-48.4% higher than the options. In the Ortapishar Tashkentskaya 10 variety (20.04), the yield obtained from the control variant is 11.8-34.4% higher than all variants, and in the Fresco F 1 hybrid, the maximum yield was 65.7 ha/t in the variant planted on April 20. was 3.8-48.0% higher than other options.